An analysis of youth crime and employment patterns - Good, David H. (Journal of quantitative criminology, 1986)
This paper investigates the relationships between the employment and the crime decisions of youths. We assume that youths maximize expected utility and we allow divergence between ex ante and ex post time allocations to legal and illegal activities. This gap motivates the exclusion restrictions which allow us to explore feedbacks between criminality and employability. Moreover, by using a panel of individual-level data, we are able to investigate the impact of historical crime and labor-market activities on the current delinquency and employability of juveniles. The measures of the endogeneous variables of our model are dichotomous. Furthermore, our sample is choice-based. Maximum-likelihood procedures which deal with these complications are used in our empirical investigations.